Building adaptive capacity in Assam - Banerjee, S; Bisht, S; Mahapatra, B (Refugee Studies Centre, University of Oxford, 2015)
A starting point for adapting to longer-term climate change could be adaptation to shortterm climate variability and extreme events. Making more informed choices about the use of remittances can enhance the adaptive capacity of remittance-receiving households.